Crocodilianos do Centro-Oeste do Brasil : ecologia populacional e aspectos genéticos sobre jacarés do trecho superior da Bacia do Rio Paraguai, Mato Grosso, Brasil - Mudrek, Jessica Rhaiza (2020)
The environmental changes resulting from the loss and removal of habitat, especially the riparian forest, installation of hydroelectric plants, urbanization, among other anthropic impacts, have drastically affected the natural populations of crocodilians. In this sense, effective conservation measures can and should be taken through assessments of conservation status, which are carried out based on information on current and past geographic distribution and various population parameters. In order to have concise information, data sources referring to the life history of species are necessary, including studies on natural history, habitat, ecological preferences, health aspects, description of the main threats and studies on population structure based on chromosomal and molecular markers. In this study, we conducted research in the Brazilian Midwest, on conservation of the six species of crocodilians, population ecology of Caiman yacare and Paleosuchus palpebrosus, morphometry of C. yacare, cytogenetics and transferability of microsatellites from P. palpebrosus. We present which threats and initiatives for the conservation of crocodilians in the Brazilian Midwest, whose units do not yet have a state list of threatened fauna. Regarding the official threat status in Brazil, none of the six Brazilian species is considered threatened and all were evaluated as LC - Least Concern. We also evaluated some population parameters such as density, sex ratio and age structure of C. yacare and P. palpebrosus, along the Paraguay River. We also verified if the use of the soil around the river influences the population parameters and the catch rates of the studied species. Caiman yacare was the most abundant species in relation to P. palpebrosus, which seems to be related to the width of the river and the use of the soil. In environments without any degree of modification, the capture rate, abundance and density are higher when compared to environments already modified. We list the morphometric measures, sex ratio and body condition of C. yacare, on the Paraguay River. We found positive and significant results between Total Length (CT) and Rostrum-Cloacal Length (CRC) with the other morphometric measures and we detected that most of the individuals who had low condition factor were newborns. The sex ratio was predominant for males, however, it would still be appropriate to search for information on what would be the appropriate sex ratio in natural populations of C. yacare. In addition, we present results of a redescription of the karyotype macrostructure of individuals from Paleosuchus palpebrosus, plus a study of chromosomal bandings. The results differ very little from that presented in a single study conducted with P. palpebrosus. We tested the transferability of microsatellites developed for P. trigonatus, Caiman crocodilus, C. latirostris, C. yacare, and Crocodylus porosus. The transferability of most microsatellites developed for P. trigonatus was positive for P. palpebrosus, with polymorphism in its results. Microsatellites that showed positive transferability can be used in population and multipaternity genetic studies. The results of this study fill gaps in different information, and can serve as relevant information to assist in mitigation measures for the conservation of Brazilian crocodile species.